2011
DOI: 10.1016/s1470-2045(10)70295-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of an RNA expression signature derived from cell cycle proliferation genes in patients with prostate cancer: a retrospective study

Abstract: SUMMARY Background Optimal management of clinically localized prostate cancer presents unique challenges because of its highly variable and often indolent natural history. To predict disease aggressiveness, clinicians combine clinical parameters to create prognostic models, but the accuracy of current models is very limited. There is significant clinical need for biomarkers that improve our ability to predict disease outcome. Methods Using quantitative RT-PCR on RNA from formalin fixed paraffin-embedded tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
692
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 705 publications
(740 citation statements)
references
References 35 publications
20
692
4
5
Order By: Relevance
“…Finally, we made an attempt to compare the performance of SigMuc1NW to Prolaris (cell cycle progression/CPC) (Cuzick et al ., 2011) in predicting BCR. The basis for this comparison was the similarities between SigMuc1NW to CPC: (a) like CPC, SigMuc1NW affects cell cycle progression (Table S2A and S2C; also see Discussion), and (b) similar to CPC, SigMuc1NW predicts BCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we made an attempt to compare the performance of SigMuc1NW to Prolaris (cell cycle progression/CPC) (Cuzick et al ., 2011) in predicting BCR. The basis for this comparison was the similarities between SigMuc1NW to CPC: (a) like CPC, SigMuc1NW affects cell cycle progression (Table S2A and S2C; also see Discussion), and (b) similar to CPC, SigMuc1NW predicts BCR.…”
Section: Resultsmentioning
confidence: 99%
“…Between two commercially available multigene panels, Oncotype DX (12 genes plus 5 reference genes) and Prolaris (31 genes), there are no overlapping genes (Cuzick et al ., 2011; Knezevic et al ., 2013). This suggests the coexistence of different genesets with predictive values toward PC recurrence, which might be attributable to the complex mechanisms involved in disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there has already been some success in the identification of subtypes of prostate cancer based on derived sets of signature gene clusters. 44,45 Numerous studies reviewed here strongly suggest that CTAs are good candidates to establish a gene signature that can predict prostate cancer progression as a result of their advanced stage specific and coordinate expression pattern. In the future, CTA gene signatures might complement clinicopathological factors in the molecular differential diagnosis of aggressive and indolent prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
“…This gene signature was initially derived from a set of 126 candidate genes associated with CCP pathways and narrowed down based on analyses of correlation among the candidate genes. The CCP signature has been evaluated in formalin-fixed paraffin-embedded (FFPE) PCa specimens derived from both radical prostatectomy and prostate biopsy specimens [31]. In clinical validation studies, the CCP signature has demonstrated favorable performance for the prediction of downstream oncologic endpoints.…”
Section: Prolarismentioning
confidence: 99%